Editorial - Ann-Kristin Kölln; Antony Mason; Maria Lenk; Jörg Tremmel; Markus Rutsche (Intergenerational Justice Review, 2018)
Among the many headlines that followed the 2018 midterm elections in the United States, one stood out as very good news for political representation: the election of Alexandria Ocasio-Cortez. Irrespective of one’s political leanings – Republican or Democrat – it is an extraordinary achievement for a 29-year-old woman and daughter to a Puerto Rican to be elected into the House of Representatives. Against a predominantly old, male, and white sitting Congress, her election means a step towards better representation of certain demographics in American policy-making processes.